Legal Crossroads for Women and Children: Safeguards or Systemic Neglect? - Hasyim, Much; Dewi, Nourma; Aini, Firstnandiar Glica (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The protection of children and women as vulnerable groups is a constitutional mandate enshrined in Article 28C of the 1945 Constitution of Indonesia, and it reflects both universal human rights principles and the foundational values of Pancasila. This study aims to examine the alignment of national legal norms with universal human rights standards, assess the effectiveness of legal protections afforded to children and women, and identify regulatory and implementation gaps that contribute to structural injustice. Employing a normative-juridical approach and analyzing five case studies of violence, the findings reveal that while Indonesia's legal framework is relatively progressive, its implementation remains hindered by institutional, socio-cultural, and political challenges. The study concludes that legal reform, institutional strengthening, and a more victim-centered legal approach are essential to achieving substantive justice for vulnerable populations. These findings provide important insights for the development of more comprehensive and impactful legal policy frameworks.